Econometric models of asymmetric ascending auctions - Han Hong; Matthew Shum (The Johns Hopkins University, Department of Economics, 2001)
We develop econometric models of ascending (English) auctions which allow for both bidder asymmetries as well as common and/or private value components in bidders' underlying valuations We show that the equilibrium inverse bid functions in each round of the auction are implicitly defined (pointwise) by a system of nonlinear equations so that conditions for the existence and uniqueness of an increasing-strategy equilibrium are essentially identical to those which ensure a unique and increasing solution to the system of equations We exploit the computational tractability of this characterization in order to develop an econometric model thus extending the literature on structural estimation of auction models Finally an empirical example illustrates how equilibrium learning affects bidding during the course of the auction.
Keywords: C51; D44; D82; L96; 330; Asymmetric auctions; Ascending (English) auctions; Simulation estimation; Auktionstheorie; Schätztheorie; Theorie